A Little Pharmacist (APOCIL) - Yulistia Budianti Soemarie; Hasniah Hasniah; Karina Erlianti; Didi Susanto (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2022)
It is very important to introduce the pharmacist profession too early in childhood, one of which is a Little Pharmacist program in elementary schools. The purpose of this community service is to introduce the pharmacist profession, especially to students at Sungai Miai 10 Elementary School Banjarmasin so that they are more familiar with and foster interest in the pharmacist profession. The stages of this activity start from a survey of the implementation location, making activity permits, preparation and implementation of activities as well as analysis of results and conclusions. The method used in this activity is the lecture method, and discussion, accompanied by training in making puyer. Participants who take part in this program are grade 5 students, totaling 31 people. The results obtained were that all participants were very enthusiastic about the pharmacist profession introduction program and after participating in this program, participants better understood the duties and responsibilities of the pharmacist profession